Power, hermeneutics and language. An analysis from The Name of the Rose of Umberto Eco - Soto Posada, Gonzalo (Estudios de Filosofía, 1999)
Based on Umberto Eco’s The name of the Rose, an attempt is made at showing the relationship between power, knowledge and language, using the figure of a rhizome type labyrinth with neither a center nor a periphery, always capable of receiving a structure, but never structured. In order to achieve this, two hermeneutic paradigms are proposed, so as to decipher the texts as a labyrinth. The first one is symbolized in Jorge de Burgos: every text is monosemantic and unidimensional, which politically leads to Jacobin and dogmatic fanaticisms. The second one is materialized in William of Baskerville: texts are polysemantic and their semiosis is unlimited, so there are no definitively written, read and interpreted texts. lt is necessary to inhabit the world from the point of view of doubt as a joyful search ad infinitum, which is translated politically into a struggle against all types of Jacobinism. The conclusion drawn from this last paradigm being tlzat hermeneutics dwell in texts since Babel, not since Pentecost. lt is the contrast between the hermeneutic seriousness of Burgos and the hermeneutic smile of Baskerville.